Reforming or re-inventing schools? key issues in school and system reform - MacBeath, John E. C.; Galton, Maurice J.; Bangs, John 1949- (Routledge, 2020)
"What has changed and what will change in the next decade? Reforming or Re-inventing Schools revisits some of the key issues in school and system reform, with a reflection of international developments to those in the English education system. It offers an insightful review and critique of education principles and their relationship to school practice, exploring some of the myths as well as examining the potential value of comparative data. Drawing on new evidence and interviews with a group of policy makers and academics on the British and international stages, this book asks: What do parents, children and 'society' want from a system of education? What motivates teachers to join the profession and why do such large numbers leave so soon? What are the roots of misunderstanding and mismanagement in provision, support and accountability? How do teachers communicate, support and exchange ideas with each other? How do we measure positive change? Examining the roots and conditions for growth, and comparing and contrasting the situation in the UK with innovative development taking place elsewhere in Europe and Asia, Reforming or Re-inventing Schools is an essential read for anyone interested in school and country performance at a national and international level"--
Description based on online resource; title from digital title page (viewed on December 20, 2019)
Keywords: Educational change / Great Britain; Educational change; Education and state / Great Britain; Education and state; School improvement programs / Great Britain; School improvement programs